2013
DOI: 10.1016/j.fra.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and DNA damage protecting activities of Eulophia nuda Lindl.

Abstract: Introduction: In recent years, natural antioxidants have seen an unprecedented importance and demand in bio-pharmaceuticals, nutraceuticals besides their use as food additives. Antioxidants act as potential prophylactic and therapeutic agents against various diseases caused by free-radicals. Plants offer tremendous source of antioxidants and are therefore being evaluated for their potentials. Eulophia nuda is an important medicinal plant used by local healers in India; however its antioxidant properties have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 25 publications
4
33
0
Order By: Relevance
“…H 2 SO 4 under nitrogen atmosphere at 120°C for a period of 6 h to afford 3,4-dihydro-6-methyl-4-phenyl-2H-benzopyran-2-one (3). Reduction of 3 with NaBH 4 in methanol produced 2-(3-hydroxy-1-phenylpropyl)-4-methylphenol (4). Phosphorylation of 4 with P(O)Cl 3 afforded the monochloride (5), which was subsequently condensed with amines to obtain the 2-amino derivatives of the title compounds 6a-j.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 SO 4 under nitrogen atmosphere at 120°C for a period of 6 h to afford 3,4-dihydro-6-methyl-4-phenyl-2H-benzopyran-2-one (3). Reduction of 3 with NaBH 4 in methanol produced 2-(3-hydroxy-1-phenylpropyl)-4-methylphenol (4). Phosphorylation of 4 with P(O)Cl 3 afforded the monochloride (5), which was subsequently condensed with amines to obtain the 2-amino derivatives of the title compounds 6a-j.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of 2-(3-hydroxy-1-phenylpropyl)-4-methylphenol (4). Two grams of compound 3 was taken in a 100-mL round bottomed flask.…”
Section: Methodsmentioning
confidence: 99%
“…They reported values of phenolic compounds between 10.8 and 56.5 mg/ g DW of herb. Kumar et al (2013) reported that the total phenolic content of Eulophia nuda in acetone and methanol extracts were higher than in aqueous extract. Our results also largely supported these conclusions.…”
Section: Discussionmentioning
confidence: 98%
“…A small quantity of the above two homogenates were separately mixed with 10% trichloroacetic acid (TCA), shaken well, centrifuged and the precipitate was used to estimate the total protein in the tissues. LPO product MDA formation was assayed by thiobarbituric reactive substance formation method [35] . The TBA-MDA chromophore was taken as an index of LPO, which gives a pink colour, which was measured at 535 nm and the results were expressed in nanomoles of MDA per mg protein.…”
Section: Tissue Lpomentioning
confidence: 99%